The timing of basaltic volcanism at the Apollo landing sites. (1st December 2019) - Snape, Joshua F.; Nemchin, Alexander A.; Whitehouse, Martin J.; Merle, Renaud E.; Hopkinson, Thomas; Anand, Mahesh
Abstract: Precise crystallisation ages have been determined for a range of Apollo basalts from Pb-Pb isochrons generated using Secondary Ion Mass Spectrometry (SIMS) analyses of multiple accessory phases including K-feldspar, K-rich glass and phosphates. The samples analysed in this study include five Apollo 11 high-Ti basalts, one Apollo 14 high-Al basalt, seven Apollo 15 low-Ti basalts, and five Apollo 17 high-Ti basalts. Together with the samples analysed in two previous similar studies, Pb-Pb isochron ages have been determined for all of the major basaltic suites sampled during the Apollo missions. The accuracy of these ages has been assessed as part of a thorough review of existing age determinations for Apollo basalts, which reveals a good agreement with previous studies of the same samples, as well as with average ages that have been calculated for the emplacement of the different basaltic suites at the Apollo landing sites. Furthermore, the precision of the new age determinations helps to resolve distinctions between the ages of different basaltic suites in more detail than was previously possible. The proposed ages for the basaltic surface flows at the Apollo landing sites have been reviewed in light of these new sample ages. Finally, the data presented here have also been used to constrain the initial Pb isotopic compositions of the mare basalts, which indicate a significant degree of heterogeneity in the lunar mantle source regions, even among the basalts collected at individual landing sites.